2013
DOI: 10.13179/canchemtrans.2013.01.01.0011
|View full text |Cite
|
Sign up to set email alerts
|

T ravelling and Source Point Identification of Some Transboundary Air Pollutants by Trajectory Analysis in Sathkhira, Bangladesh

Abstract: It is evident from the study that transboundary traveling has a significant effect on air quality and the pollutants traveled firmly beyond the boundary line of Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Because of wind direction in the dry season (North, North-westerly wind mainly dominate which travel over the polluted region of India and then enter Bangladesh) and the long-range traveling ability of PM-2.5, the transboundary effect contributes significantly to PM concentration in Bangladesh [16]. A few studies [12][17] [18] revealed that the air of Dhaka city is getting some unwanted PM-2.5 from other countries through long-range air mass traveling. This study aims to find out the probable contribution of long-range transportation of PM-2.5 on Dhaka's atmosphere during the time interval from November-2019 to April-2020.…”
Section: Introductionmentioning
confidence: 99%
“…Because of wind direction in the dry season (North, North-westerly wind mainly dominate which travel over the polluted region of India and then enter Bangladesh) and the long-range traveling ability of PM-2.5, the transboundary effect contributes significantly to PM concentration in Bangladesh [16]. A few studies [12][17] [18] revealed that the air of Dhaka city is getting some unwanted PM-2.5 from other countries through long-range air mass traveling. This study aims to find out the probable contribution of long-range transportation of PM-2.5 on Dhaka's atmosphere during the time interval from November-2019 to April-2020.…”
Section: Introductionmentioning
confidence: 99%